Purple Glove Syndrome- A Catastrophic Complication of Phenytoin Injection - Vivek Lahane; Ruchita Kabra; Anmol Andhale; Sourya Acharya; Sunil Kumar (Journal of Clinical and Diagnostic Research, 2023)
Purple Glove Syndrome (PGS) is a rare complication of intravenous phenytoin administration, which is illustrated by delayed soft tissue injury of the skin conterminous to the point or distal to the site of intravenous phenytoin infusion. The clinical features of PGS include pain, oedema, and bluish discolouration over the extremity. The present case report describes about a 60-year-old male, who presented to the Emergency Department with the chief complaints of generalised tonic clonic seizures, lasting for 10 minutes, for which he was managed with inj. phenytoin sodium. The computed tomography scan of brain revealed right-sided subdural haematoma. After 24 hours of hospital stay, the patient started complaining of severe pain in the arm and forearm. There was purple-bluish discolouration around the intravenous site, peripheral oedema and pain. The various risk factors linked to PGS, include old age and large and multiple doses of phenytoin.